How does online interactional unfairness matter for patient–doctor relationship quality in online health consultation? The contingencies of professional seniority and disease severity. Issue 3 (4th May 2019) - Zhang, Xiaofei; Guo, Xitong; Lai, Kee-hung; Yi, Wu
ABSTRACT: In recent years, the development of online health-consultation platforms has drawn significant research attention to online patient–doctor relationship development, particularly in developing countries, where there are limited health care resources for each patient. However, online interactional unfairness in patient–doctor relationship development has been largely overlooked in the context of information and communication technology (ICT). This study proposes and tests a model that examines how online interactional unfairness (ie, interpersonal unfairness and informational unfairness) influences online patient–doctor relationship quality and the contingent roles of a doctor's professional seniority and a patient's disease severity. Using archival data with 83, 553 observations from a leading online health-consultation platform in China, this study employed rare-event logistic regression to test the model. The results show that online interpersonal unfairness and online informational unfairness have negative and positive effects on relationship-quality incentive, respectively, in the Chinese health care context and that a doctor's professional seniority and a patient's disease severity strengthen the link between unfairness perceptions and relationship-quality incentive. This study advances the knowledge of online patient–doctor relationship development in ICT-based health care in China and provides practical insights for online health care stakeholders for managing unfairness in the health care context.